The Materials Science beamline upgrade at the Swiss Light Source. (15th July 2013) - Willmott, P. R.; Meister, D.; Leake, S. J.; Lange, M.; Bergamaschi, A.; Böge, M.; Calvi, M.; Cancellieri, C.; Casati, N.; Cervellino, A.; Chen, Q.; David, C.; et al.
Abstract : The Materials Science beamline at the Swiss Light Source has been operational since 2001. In late 2010, the original wiggler source was replaced with a novel insertion device, which allows unprecedented access to high photon energies from an undulator installed in a medium‐energy storage ring. In order to best exploit the increased brilliance of this new source, the entire front‐end and optics had to be redesigned. In this work, the upgrade of the beamline is described in detail. The tone is didactic, from which it is hoped the reader can adapt the concepts and ideas to his or her needs.